Echocardiographic predictors of first onset of atrial fibrillation in dogs with myxomatous mitral valve disease. (7th August 2020) - Baron Toaldo, Marco; Mazzoldi, Chiara; Romito, Giovanni; Poser, Helen; Contiero, Barbara; Cipone, Mario; Guglielmini, Carlo
Abstract: Background: Atrial fibrillation (AF) occurs in dogs with myxomatous mitral valve disease (MMVD) as a consequence of left atrial (LA) dilatation, and it affects survival and quality of life. Objectives: To evaluate the usefulness of echocardiography in predicting the first occurrence of AF in dogs with MMVD. Animals: Forty‐four client‐owned dogs with MMVD, 22 dogs that developed AF, and 22 dogs that maintained sinus rhythm. Methods: Retrospective observational study. Medical databases were reviewed for dogs that developed AF during the year after diagnosis of MMVD (AF group). The last echocardiographic examination obtained while still in sinus rhythm was used to derive selected variables. For each dog with AF, a control dog matched for body weight, class of heart failure, and LA dimension was selected. Echocardiographic results including LA volumes and LA speckle tracking echocardiography (STE)‐derived variables were measured. Results: Among the tested echocardiographic variables, only LA diameter ( P = .03) and left ventricular internal diameter in diastole ( P = .03) differed significantly between groups, whereas body weight‐indexed variables of cardiac dimension as well as LA volumes and volume‐derived functional variables were not different. Among the STE‐derived variables, peak atrial longitudinal strain (PALS) results differed significantly between the AF group (23.8% ± 8.6%) and the control group (30.5% ± 9.6%; P = .03). A value of PALS ≤28% predicted AF occurrence with sensitivity and specificity of 0.80 and 0.65, respectively. Conclusions and Clinical Importance: Absolute cardiac diameters and LA STE (in particular, PALS) are useful echocardiographic predictors for the development of AF in dogs with MMVD.